Patient Portal Privacy: Perspectives of Adolescents and Emerging Adults Living with HIV and the Parental/Guardian Role in Supporting Their Care - Jackman, Kevon-Mark P.; Ohene-Kyei, Elise Tirza; Barfield, Ashle; Atanda, Fopefoluwa; Smith, Raina; Huettner, Steven; Agwu, Allison; Trent, Maria (Applied Clinical Informatics, 2023)
Background Increasing the percentage of people living with human immunodeficiency virus (HIV), including youth, who are virally suppressed to 95% is an overall goal of the ending the HIV epidemic initiative. While patient portals have become ubiquitous, questions remain about how best to operationalize parental/guardian access to youth's patient portals in alignment with optimizing HIV care outcomes and patient preferences. This qualitative study focuses on understanding perspectives among youth with HIV (YHIV) about parental access to patient portals.Methods Eligible participants were YHIV aged 13 to 25 years receiving care at an urban academic hospital. Semistructured individual/paired interviews were conducted between May 2022 and March 2023. Participants were asked to discuss thoughts on parental access to patient portals, and roles parents/guardians have in supporting their HIV care. Semistructured interviews were conducted with adolescent and emerging adult health care workers (HCWs) to gain perspectives on YHIV emergent themes. Audio-recorded interviews were transcribed verbatim, and we conducted thematic analysis using an inductive approach to identify codes and themes.Results Sixteen YHIV and four HCWs participated in interviews. Parental roles in coordinating HIV care ranged from supporting YHIV needs for transportation, acquiring, and taking medications, to not having any role at all. Participants shared heterogeneous perspectives about their openness to share patient portal access with their parents/guardians. Perspectives were not strictly congruent along lines of participant age or parental roles in helping youth to manage HIV care. Sharing passwords emerged both as a pathway that YHIV grant access to their accounts and a source of confusion for clinicians when parents/guardians send messages using their child's account.Conclusion Findings suggest HCWs should initiate conversations with YHIV patients to determine preferences for parental/guardian access to their patient portal, educate on proxy access, and explain the extent of medical information that is shared with proxy accounts, regardless of age and perceived parental involvement in HIV care.
Keywords: patient portal; electronic health records and systems; adolescent medicine; infectious disease; families of patients; patients with chronic illness or special needs; personal health records